Value Investing: A New SCORE Model - Navas, D., Raúl; Bentes, R., Sonia (Review of Business Management, 2023)
Purpose – We propose a new SCORE model, inspired by Piotroski’s (2000) well-known F-SCORE. But here we examine past, present, and future earnings forecasts in this binary model, which is also made up of nine signals. Theoretical framework – This research investigates whether a basic accounting-based fundamental analysis method can affect the distribution of returns earned by an investor when applied to a board portfolio of higher growth stocks with high fundamentals (book value). Design/methodology/approach – At the end of the fiscal year, we determine the market value of the equity and the BM of the Euronext 100 companies. After forming the BM, we keep the organizations with the highest BM and enough financial statement data to calculate the various performance indicators. The analysis covers the years from 2000 to 2020, a period of 21 years. Findings – We demonstrate that by selecting businesses with strong fundamentals, a high SCORE investor’s yearly mean return can be boosted by at least 30%. Practical & social implications of research – Concerning the study’s weaknesses, one of them is the high SCORE of the model providing limited data, which may skew the conclusions. Originality/value – This study illustrates how, when applied to a board portfolio of high book-to-market firms with growth potential, a simple accounting-based fundamental strategy can alter the distribution of returns earned by an investor. Keywords – capital markets; market efficiency; fundamental analysis; European markets; growth stocks.